How smart experiences build service loyalty: The importance of consumer love for smart voice assistants. Issue 7 (21st April 2021) - Hernandez‐Ortega, Blanca; Ferreira, Ivani
Abstract: Smart voice assistants (SVAs) have emerged as new artificial intelligence service platforms. They have the capacity to act like actual human assistants and modify traditional forms of human–computer interactions. So, consumers relate to their SVA as though it was a person, despite knowing that they are interacting with a machine. Based on the stimulus‐organism‐response framework, this paper examines feelings of love that consumers develop for SVAs when they are interacting. It proposes that these feelings act as the psychological mechanism to transmit the effect of consumers' experiences with the technology (i.e., smart experiences) on their service loyalty. Feelings of love are conceptualized following the triangular theory of love that considers three components: passion, intimacy, and commitment. Service loyalty refers to consumers' intentions to continue using SVAs in the future and to recommend SVAs to other people through physical and/or electronic word of mouth communication. The results show that smart experiences influence consumers' passion for technology, while passion explains their intimacy and commitment. Consumer intimacy and commitment for SVAs lead to service loyalty. Therefore, this paper contributes to research focusing on the importance of consumers' feelings for SVAs and shedding light on the process that drives to service loyalty.